A meta-analysis of health effects of randomized controlled worksite interventions: Does social stratification matter? - Diego Montano; Hanno Hoven; Johannes Siegrist (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: The aim of this review was to assess what types of socioeconomic positions (SEP) are being considered in randomized controlled intervention studies and estimate the moderation of SEP in workplace intervention effects on body mass index (BMI), fruit and vegetable consumption, musculoskeletal symptoms, and job stress. METHODS: A meta-analysis of randomized controlled workplace interventions was undertaken. Studies were classified by participants' SEP. The overall standardized mean difference (SMD) for each outcome was estimated with random-effects models. Additionally, a random-effects model with SEP as moderating variable was calculated in order to assess intervention effect modification (EM). RESULTS: This review covers 36 studies. Altogether 40 reports of intervention effects were considered. The overall mean differences in the models, without SEP as moderating variable, were significant for all outcomes. BMI, self-reported musculoskeletal symptoms, and self-reported job stress decreased [SMD -0.16, 95% confidence interval (95% CI) -0.29- -0.02, SMD -0.32, 95% CI -0.51- -0.14, and SMD -0.37, 95% CI -0.71- -0.04, respectively], whereas daily consumption of fruit and vegetables increased (SMD 0.12, 95% CI 0.01-0.22). There were no statistically significant differences between occupational classes for the health outcomes considered (SMD -0.102, 95% CI -0.264-0.060, EM -0.141, 95% CI -0.406-0.125; SMD 0.117, 95% CI -0.049-0.282, EM 0.000, 95% CI -0.230-0.231; SMD -0.301, 95% CI -0.494- -0.107, EM -0.369, 95% CI -1.169-0.430; and SMD -0.200, 95% CI -0.524-0.124, EM -0.598, 95% CI -1.208-0.012, respectively). CONCLUSIONS: Workplace interventions can achieve small positive effects on major health outcomes. We could not confirm whether these effects are moderated by occupational class.